Enzymatic Assembly of Overlapping DNA Fragments - Gibson, Daniel G. (Methods Enzymol, 2011)
Three methods for assembling multiple, overlapping DNA molecules are described. Each method shares the same basic approach: (i) an exonuclease removes nucleotides from the ends of double-stranded (ds) DNA molecules, exposing complementary single-stranded (ss) DNA overhangs that are specifically annealed; (ii) the ssDNA gaps of the joined molecules are filled in by DNA polymerase, and the nicks are covalently sealed by DNA ligase. The first method employs the 3′-exonuclease activity of T4 DNA polymerase (T4 pol), Taq DNA polymerase (Taq pol), and Taq DNA ligase (Taq lig) in a two-step thermocycled reaction. The second method uses 3′-exonuclease III (ExoIII), antibody-bound Taq pol, and Taq lig in a one-step thermocycled reaction. The third method employs 5′-T5 exonuclease, Phusion(®) DNA polymerase, and Taq lig in a one-step isothermal reaction and can be used to assemble both ssDNA and dsDNA. These assembly methods can be used to seamlessly construct synthetic and natural genes, genetic pathways, and entire genomes and could be very useful for molecular engineering tools.